Removable singularities of mappings with inverse Poletsky inequality on Riemannian manifolds - Desyatka, V.; Sevost’yanov, E. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC517.5 We consider open discrete mappings of Riemannian manifolds satisfying a certain modulus inequality. We analyze the possibility of continuous extension of these mappings to an isolated point of the boundary. It is proved that these mappings admit extensions of this kind if they exclude two or more points of the connected Riemannian manifold and the majorant appearing in the modulus inequality is integrable over almost all spheres.